Investigating 'optimal' kriging variance estimation :analytic and bootstrap estimators - Ngwenya, Mzabalazo Z (Department of Statistical Sciences, 2015)
Kriging is a widely used group of techniques for predicting unobserved responses at specified locations using a set of observations obtained from known locations. Kriging predictors are best linear unbiased predictors (BLUPs) and the precision of predictions obtained from them are assessed by the mean squared prediction error (MSPE), commonly termed the kriging variance.